Denial of the exequatur of the foreign judgment on the paternity of minors born through surrogacy: Regarding the Judgement of the Suprem Court of 4th December 2024 - Castellanos Ruiz, Mª José (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In Judgment 1626/2024, of December 4, 2024, the Supreme Court rejected the exequatur of a foreign judgment validating a surrogacy contract and attributing paternity of the children to the intended parents, because it is contrary to public policy. The fundamental rights and constitutional principles enshrined in Title I of the Constitution, which include the rights to physical and moral integrity of the surrogate mother and the child, and respect for their dignity, constitute this public policy that prevents the recognition of foreign decisions.In this case, the Supreme Court adds that in the United States, surrogacy constitutes a huge business in which the intended parents disburse significant amounts of money, a portion of which is received by the surrogate mother. Therefore, consent before birth has been obtained through some form of compensation. In my opinion, the Supreme Court is mistaken, because surrogacy cannot be approached in such a general way, but rather must be addressed individually. As the ECHR pointed out in the Mennesson and Labassee cases, a restrictive and specific conception of international public order must be followed.
Keywords: Surrogacy; surrogate motherhood; conflict-of-laws; recognition and enforcement of foreign decisions; foreign birth certificates; paternity; Private international law; international public policy; interests of the child